Syariah fintech lending as a profit sharing-based MSMEs funding solution in the era of society 5.0 - Poppy Wulandari; Ulan Dari Daulay; Anisha Hardianti; Aboubaker Khoualed (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study aims to investigate the innovation of sharia fintech lending as a solution to the funding challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on the application of profit-sharing financing models and their impact on MSME development in the Society 5.0 era. A Systematic Literature Review (SLR) methodology was employed, utilizing the PRISMA framework to identify, screen, and evaluate relevant studies published within the last five years. The review process resulted in the inclusion of 21 articles that formed the foundation for this study. The findings indicate that MSMEs in Indonesia face significant barriers to funding from conventional financial institutions due to high interest rates and stringent collateral requirements. Sharia fintech lending, utilizing profit-sharing models such as mudharabah and musyarakah, emerges as a fairer and more accessible alternative, promoting financial inclusion and addressing the unique needs of MSMEs. The study highlights the potential of sharia fintech lending to enhance financial inclusion and drive economic growth by providing MSMEs with easier access to financing without the constraints of conventional banking. It recommends further development of digital infrastructure and collaboration among stakeholders to expand the adoption of sharia fintech lending, fostering sustainable economic growth.